LETTER FROM A HUNCHBACK GIRL: FERNANDO PESSOA, MARIA JOSÉ, AND THE FACTLESS AUTOBIOGRAPHY - Gary Scudder (PEOPLE: International Journal of Social Sciences, 2025)
The brilliant Portuguese poet Fernando Pessoa created many heteronyms, four of which – Alberto Caeiro, Álvaro de Campos, Ricardo Reis, and Pessoa himself - could easily vie for the title of Best 20th Century Portuguese Poet. However, this is only four of dozens and dozens of heteronyms that grew out of Pessoa’s rich imagination. Only the last of these heteronyms, Maria José, a nineteen-year-old hunchback girl, dying of tuberculosis, was female. Pessoa’s entire literary production while writing as Maria José was one unpublished letter, detailing her sadness while sitting at her window and staring out at a worker who doesn’t know she exists. Scholars have noted the significance of Maria Jose’s gender, especially in light of Álvaro de Campos’s bisexuality. Others have discussed the role of Maria José as a literary substitution for Pessoa himself, her isolation mirroring his own. This paper will build upon that theme, exploring the “Letter from a Hunchback Girl to a Metalworker” as a “factless autobiography.” Pessoa used the term “factless autobiography” to identify his The Book of Disquiet, a work that he attributed to another heteronym, or semi-heteronym, Bernardo Soares. Essentially, Pessoa freed himself from the tyranny of actual, specific names and dates, which allowed him to delve to incredible depths. This paper will explore not only Maria José’s letter as a farewell to the heteronyms, but also its role as a “factless autobiography” in its own right.